Ang Pagkalalaki ayon sa Mga Lalaki: Pag-Aaral sa Tatlong Grupong Kultural sa Pilipinas - & Mariano R. Sto. Domingo, Grace Dalisay, Ma. Lina Van Heugten (Philippine Social Sciences Review; Gender Issues in Philippine Society, Ed., Ma. Cecilia Gastardo-Conaco, 2010)
This study looked into how Filipino males from three cultural groups-the Tagalogs, Ilonggos and Maranaws, differ in their understanding of the concepts of pagkalalaki (manhood), tunay na lalaki (real man) and ganap na lalaki (fulfilled man). Responses across the 3 cultural groups appear to be similar in terms of the biological aspects of manhood as manifested in physical attributes, strength and the ability to fulfill role expectations. Differences are more pronounced in the cultural and psycho-social realms.